E-textiles: An interdisciplinary approach: Problem solving in an educational context - Strand, Kari Saasen; Haakonsen, Peter; Fauske, Laila Belinda (FormAkademisk, 2020)
This article aims to shed light on e-textiles as a fusion of different skills. The empirical starting point is a workshop on e-textiles offered to a group of teachers attending a continuing education course in art and design. The study adopts self-ethnography. Using anonymous reflection notes from the workshop, the article discusses e-textiles as an arena to enhance problem solving through practical explorational work. This involves interdisciplinarity, crafting skills and computational thinking. Focusing on two categories, namely I) material knowledge and sustainability and II) electronics knowledge and interdisciplinarity, this study shows that time is an important factor when exploring e-textiles in an educational context. In e-textiles, crafting, circuitry, programming and sustainable thinking can be combined in an interdisciplinary and productive mash-up encouraging problem solving.